The Tradition of Nginjeum Panganten in the Perspective of al ‘Urf: Analysis of Sundanese Customary Practices in Tasikmalaya, Indonesia - Heni Purnama Sari; Badruzzaman (CV. FOUNDAE, 2025)
Marriage is a legal and social institution governed by religious norms, customs, and positive law, with the aim of forming a family that is sakinah, mawaddah, and rahmah. In the Sundanese traditional community in Mekarjaya Village, Padakembang District, Tasikmalaya Regency, there is a marriage practice called Nginjeum Panganten, which is a tradition where the reception and wedding procession are held at the groom's residence with the bride attending from her residence. This study aims to analyze the practice of Nginjeum Panganten from the perspective of Islamic law through the concept of Al-'Urf. This study uses field research with a descriptive-analytical approach. Primary data was obtained through in-depth interviews with traditional leaders, religious leaders, and communities directly involved in the implementation of the Nginjeum Panganten tradition. Secondary data was collected through a literature review of Islamic law, customary law, and relevant scientific works. Data analysis was conducted using an inductive approach to draw normative conclusions from empirical facts. The results of the study indicate that the Nginjeum Panganten marriage practice does not conflict with the principles of Islamic law, as long as the pillars and requirements of marriage are fulfilled. This tradition can be classified as Al-'Urf Shahih, which is a custom that is generally accepted by the community and does not contradict the provisions of Sharia law. Thus, Nginjeum Panganten has legal legitimacy from both the perspective of customary law and Islamic law, and reflects the harmony between local cultural values and the principles of Islamic Sharia.